Comprendre le territoire de Venise - Lorena Rocca (Netcom)
The research project PANDORA - PArticipatory Networks and Databases fOr sustainable Research and Assessment (www.feempandora.it) – of Enrico Mattei Eni Foundation started an Action Research analysis aiming at experimenting innovative forms of participation through the use of ICTs, especially through an on-line space meant to spread news and data about the town but also, most of all, to collect voices, perceptions, ideas and possible alternative ways towards a development which should be, at the same time, sustainable and shared.